View of Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
Photo showing an aerial view of Port of Spain, Trinidad.
Colour: Black and White ; Style: Landscape ; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Port of Spain